Lawyers on trial understanding ethical misconduct - Abel, Richard L. (New York ; Oxford : Oxford University Press, 2011)
Richard L. Abel presents the stories of ten California lawyers who broke the rules: hiring an ex-cop to chase ambulances flouting fee limitations in medical malpractice cases, creating a fictitious company and impersonating non-existent people in order to appropriate Sega's computer games.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Lawyers -- California -- Discipline; Legal ethics -- California; Practice of law -- California